ANALISIS MODEL CAPM DALAM MEMPREDIKSI TINGKAT RETURN SAHAM SYARIAH DAN KONVENSIONAL (Studi kasus Saham di Bursa Efek Indonesia) - Isnurhadi Isnurhadi (JEMBATAN, 2014)
This research is to recognize the accuracy of CAPM models in predicting the stock return of rural stocks and conventional stock at Jakarta Islamic Index and Indonesian Stock Exchange. Variable of this research are JII and LQ45 stock return, Beta, Risk free, and Market return. The accuracy of CAPM models is measured by standart deviation and t test. The population of this research is all monthly stock return JII and LQ45 already go public at Indonesian Stock Exchange. Whereas the sample used is the monthly stock return of 11 JII companies and 13 LQ45 companies during 2007 – 2012. The result of this research showes that the CAPM model is accurate in predicting the stock return JII and LQ45.Keywords: LQ45. JII, Stock Return, Beta, Risk free, Market return, and CAPM